Fifty years of Teikei: the evolution of the movement’s ten principles and its impact on alternative food initiatives in Japan - Kondo, Chika; Zollet, Simona; Kobayashi, Mai; Yamamoto, Nami (Frontiers in Sustainable Food Systems, 2024)
Introduction Japan’s teikei movement, recognized as a source of inspiration for Community Supported Agriculture (CSA) in Western countries, is now entering its fifth decade. Built upon trust and shared values, teikei has continued to rely on mutually supportive relationships between organic producers and consumers. The movement’s commitments were originally articulated through the ten principles of teikei, which offer a roadmap to create food systems based on solidarity principles going beyond market transactions. Despite a decline in numbers, teikei groups continue to operate in the midst of societal shifts that are altering food practices and consumption patterns. These changes have had an impact on the implementation of the ten principles and on the power dynamics between producers and consumers. Methods This research investigates how such shifts have affected the development of alternative food systems in Japan, the evolution of teikei as a social movement, and the tensions that arise from contrasting notions of agri-food system alterity rooted in decommodified relationships versus market-based transactions. We employ the ten principles as a framework to investigate the transformations of some representative teikei groups over time, and identify three types of shifts: relational, operational, and ideological. These shifts show how different teikei actors have been engaging in realizing the vision of building sustainable agri-food systems through alternative market relations. Results The shifts also underscore the fluid and situated nature of agri-food system alterity within historical, geographical, and cultural relational spaces. The current variations of teikei configurations and the progressive diversification of approaches to address the challenges of upholding the original principles demonstrate the movement’s adaptability over time. However, they also demonstrate the necessity to strike a compromise between conflicting needs. Discussion The development of the teikei movement is not only important from an historical and geographically-situated perspective, but also as a dynamic and evolving experiment in the potential and challenges of active food citizenship. The democratic decision-making processes embedded within teikei principles and practices offer a valuable model for understanding how individuals enact their food citizenship and contribute to ongoing transformation of the agri-food system. Simultaneously, these shifts also serve as a warning against how democratic principles can be eroded by conventionalization and neoliberalization, and about the assumptions that arise during the process of building alternative agri-food systems, such as gendered labor.